PHYSICIAN HEALTH AND WELLNESS- ASSESSMENT OF A PEER SUPPORT PROGRAM IN A WESTERN CANADIAN TERTIARY HOSPITAL PEDIATRIC DEPARTMENT - McKenzie VAN EATON (Rojan GÜMÜŞ, 2023)
Peer support programs (PSP) have been used and found to be effective in mitigating burnout by utilizing the innate tendency to respond and empathize with shared difficulty. Such a program was established in the Pediatrics department of a tertiary care hospital in the Western Canadian city of Regina in January 2021. This study evaluates the effectiveness of the peer support program and its value in managing stress among physicians. Between January and March 2021, 14 Physicians were paired to have informal virtual meetings every two weeks for three months. A mixed-methods design was used to assess the program. Once peer support sessions concluded, physicians participated in a cross-sectional survey and were interviewed to assess their experiences and perceptions of the program. Descriptive statistics were computed from survey data. Interview data were analyzed qualitatively and coded for themes based on recurring issues. Workload, lack of support, administrative work, and high-intensity cases were mentioned as some stressors by the physicians contributing to burnout. Survey findings (response rate 64%) showed that 78% of participants perceived the workplace as stressful and chose a paired over group peer support, 56% found the program helped to alleviate stress and burnout and all respondents preferred support from co-physicians compared to other health care professionals, Physicians recommend the continuation, expansion, and advocacy for the program while providing a more formal structure with administrative support for schedule integration and protected time.